Applying the TIMBUS Approach to Preserving Context in Digital Libraries - Coutinho, C.; Gooding, P. (Proceedings of the 11th Annual International Conference on Digital Preservation (iPres2014), 2014)
To date, digital preservation has generally focused on the preservation of specific data in the form of artefacts. However, in order to ensure that this data is accessible in the long term, it is vital that we consider how to extract and preserve information on the software and hardware contexts which this data depends upon to operate. We therefore need tools to assist in identifying, preserving and validating the processes which underpin the creation of data in digital libraries. In particular, we need to consider the importance of preserving not just individual digital artefacts, but the platforms which allow digital libraries to render or execute their items. Digital libraries rely on this software to render their items, and it is therefore important to know configuration details and software dependencies to ensure these items remain fully operational in the future. In the case of digital libraries, the TIMBUS framework provides the tools necessary to assist practitioners in identifying relevant processes, undertake risk analysis, and then to assist the user in extracting, preserving and revalidating the necessary processes. This half-day tutorial introduces the TIMBUS approach to process preservation, and demonstrates how it can be applied to issues relating to digital libraries. TIMBUS focuses primarily on business processes, but this tutorial will show its approach to process-oriented preservation is also relevant to digital libraries. It provides a methodology for process preservation and a set of tools which help to semi-automatically validate and preserve processes so that they can be recreated at a later date. Participants will be given the knowledge to understand the importance of technical environments for collection items, and learn more about the TIMBUS solutions through examples relevant to the digital library domain. They will also gain an understanding of digital preservation as a risk mitigation strategy.